A Compact Dual Band –Notched UWB Antenna using Inverted Tshaped Slots (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper proposes a compact printed monopole antenna with dual band-notched characteristics for ultrawideband application. The proposed antenna consist two inverted T-shaped slots in radiating patch, which provides dual band-notched characteristics and partial ground plane with a slit, which provides large usable fractional bandwidth 129% (2.8-13.1 GHz).The upper inverted T-shaped slot provides notch band for 3.5/5.5-GHz WIMAX between 3.3-4 GHz and lower inverted T-shaped slot provides notch band for 5.2/5.8-GHz WLAN between 4.6-5.9 GHz. By properly adjusting the dimension of these slots band-notched characteristics such as notch frequency and notch bandwidth can be control. The proposed antenna has size of 24×28 mm2 and provides 10 dB return loss bandwidth from 2.8 GHz to 13.1 GHz with two notched bands, covering 5.2/5.8-GHz WLAN, 3.5/5.5 GHz WIMAX. The simulated VSWR and radiation pattern of proposed antenna are presented, which prove that the proposed antenna is a good candidate for various UWB applications.